Children's right to play in Papua New Guinea: insights from children in years 3–8. Issue 2 (4th May 2018) - Simoncini, Kym; Elliott, Sue; Carr, Victoria; Manson, Elisapesi; Simeon, Lalen; Sawi, Joros
ABSTRACT: This paper describes children's participation in and perceptions of a redeveloped playground in Papua New Guinea (PNG). The playground was a partnership between three western early childhood education academics and a teacher education faculty at the Pacific Adventist University (PAU), PNG to promote children's right to play. Children in PNG are typically deterred from playing during school lunch and recess and school playgrounds mostly consist of open grassed areas. Three hundred children attending the PAU on campus primary school (Years 3–8) led the design, assisted with the build and reflected on their experiences and feelings about the playground. Both boys and girls overwhelmingly reported positive experiences and feelings towards the playground including students in Years 7 and 8 who were not permitted to use the playground. This study demonstrated that school playgrounds can enact children's right to play and that children can participate in both playground design and research in PNG.